2016
DOI: 10.1002/ajh.24303
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of CD3/CD28 costimulated umbilical cord blood T cells at the time of single umbilical cord blood transplantation may enhance engraftment

Abstract: Limited cell numbers in umbilical cord blood (UCB) grafts present a major impediment to favorable outcomes in adult transplantation, largely related to delayed or failed engraftment. The advent of UCB transplantation (UCBT) using two grafts successfully circumvents this obstacle, despite the engraftment of only one unit. Preclinical models suggested that the addition of UCB T cells at the time of transplant can enhance engraftment. We tested whether ex vivo activation by CD3/CD28 costimulation and expansion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…This supports the clinical observation that CB T cells have robust antitumor effects after adoptive T‐cell transfer . The enhanced cytotoxic activity of CB T cells and their differentiation into a more central‐effector memory phenotype might explain why CB‐activated donor lymphocyte infusion is more likely to mediate acute GVHD than PB‐activated donor lymphocyte infusion, despite improved survival …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This supports the clinical observation that CB T cells have robust antitumor effects after adoptive T‐cell transfer . The enhanced cytotoxic activity of CB T cells and their differentiation into a more central‐effector memory phenotype might explain why CB‐activated donor lymphocyte infusion is more likely to mediate acute GVHD than PB‐activated donor lymphocyte infusion, despite improved survival …”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, we found that addition of IL‐12 inhibits IL‐21–induced CD8+ T‐cell proliferation. This might be due to known interferences of the IL‐12 and IL‐21 signaling pathways . In contrast, treatment with IL‐12 alone led to the augmentation of T‐cell functionality and cytotoxicity and increased CD62L expression on MART1‐reactive CTLs generated from both graft sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no infusion-related toxicities and there was no clinically GVHD arising as consequence of the DLI. In another phase 1 trial by Hexner et al, patients with CB frozen in 2 fractions received ex vivo expanded CB T cells at 1×10 5 cells/kg (82). There was evidence of early T cell trafficking and supraphysiological levels of cytokines relevant to engraftment.…”
Section: Expanding T Cells For Donor Lymphocyte Infusion (Dli)mentioning
confidence: 99%
“…Cell therapies have been generated from tumor infiltrating lymphocytes obtained by surgical resection, from mobilized hematopoietic stem cell products, bone marrow, cord blood, and even whole blood (23, 24). Each of these sources offers a unique cost/benefit profile with respect to yield and purity.…”
Section: Collectionmentioning
confidence: 99%